The Future of Radiology through the Lens of Medical Physics: AI, Safety, and Advanced Modalities - Ahmed Mubarak Alqurashi,; Almuzun Alasmar Alanzi,; Malak Mohammad Alshammari,; Wafa Abdulrahman Obaid Altamimi,; Abdulmajeed Tariq Rajeh Alrajeh,; Fawaz Ali Nahar Alshammari,; Bandar Katib Alanizi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Radiology has long been established on the core of the diagnostics and therapy. In modern decades, rapid progress in the field has been primarily associated with the impact of medical physics, which applies the principles of physics in medicine. Future developments in radiology will be really transformed by artificial intelligence (AI), patient safety, and steady advancement in more advanced imaging modalities. Aim of work: To highlight the challenges and opportunities in these domains, emphasizing the need for integrated approaches to optimize healthcare delivery and improve patient outcomes. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Future, Radiology, Medical Physics, AI, Safety, and Advanced Modalities. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:In conclusion, from the perspective of medical physics, radiography is poised for significant innovation and change in the future. AI, improved safety protocols, and state-of-the-art imaging technology working together promises to transform the industry and improve patient outcomes while tackling major obstacles. A future in which radiology continues to be at the vanguard of medical research and patient care will be shaped by the cooperation of medical physicists, radiologists, and technologists as these developments take place.